How Watching Movies from Netflix Help Students’ Improving Language Skills - Cambelyena Julie Robert; Marlin Steffi Marpaung (Peneliti.net, 2022)
Netflix is a streaming application that is very popular to young generation, Netflix allows users to access local and international movies and films with a very diverse selection. The objective of this study is to see how Netflix affects the improvement of students’ English language skills. This study used a qualitative descriptive and the data collected were analyzed using thematic analysis by incorporating interpretive description approach. A semi-structure interview with open-ended questions is used as the instrument in this study. The respondents of the study were 15 students of Universitas Advent Indonesia taken from different faculties and purposive sampling is used in selecting the respondents. There were 11 females and 4 males in this study. The results of this study indicated that the use of the Netflix application to watch foreign films has been able to improve students’ English language skills.